Study on dynamic mechanical properties of frozen weakly cemented rock under lateral constraint - Li, Weiyu; Fang, Shizheng; Zhu, Ye; Li, Guangming (Frontiers in Materials, 2025)
Weakly cemented red sandstone is common in the construction of shaft engineering in western China. Based on the actual working conditions, the dynamic mechanical behavior of this kind of rock under the combined action of multiple variables was studied. Based on the freezing temperature of the freezing method for shaft construction, the experimental temperature gradient was set at 25°C to −25°C. Using an modified split Hopkinson pressure bar (SHPB) experimental system, the dynamic mechanical response of frozen weak-cemented red sandstone under lateral constraints was studied. Taking dynamic and static stress fields and temperature fields as the entry point, the relationship between dynamic load, confining pressure, temperature, and dynamic mechanical characteristics parameters of weakly cemented rock is established, and the strain rate effect, lateral constraint effect, and negative temperature effect of dynamic compressive strength are analyzed. The research results show that: 1) The confining pressure changes synchronously with the axial dynamic load, and undergoes three stages: rapid increase, slow increase, and unloading rebound. 2) Under the combined effects of multiple variables, the dynamic mechanical behavior of the rock shows obvious compaction and rebound characteristics. 3) The dynamic compressive strength of the rock is jointly affected by strain rate, confining pressure, and temperature. Among them, lateral constraints have a strengthening effect. The dynamic compressive strength increases exponentially with increasing strain rate, and increases first and then decreases with decreasing temperature. At the same time, the degree of rock fragmentation is consistent with its strength characteristics. The research results have certain reference significance for the engineering design and safe operation and maintenance of frozen rock structures under dynamic loading.